The companies amendment act, 1989: a panacea for insider trading? - Beningfield, P G (Department of Commercial Law, 2025)
... Our enquiries suggest that a large ring of people have dealt at the stock exchange using information (whether they have in all cases known it or not) which has ultimately derived from one particular Crown servant. The scale of the dealings in that ring is such that the value of the shares bought and sold by its members comfortably exceeds 10 million pounds. Our enquiries have also suggested, however, that there may well have been more than one Crown servant involved in disseminating unpublished price-sensitive information and that, rather than there being one ring, there has been a second ring as well, not necessarily connected with the first. .. .It is, in our view, inevitable that criminal activity relating to insider dealing will flourish if those carrying out such activities are effectively assured of anonymity and comforted by the fact that enquiries such as ours can be impeded in this all-important area. In particular, we consider the evidence relating to the very scale of the activities and the number of persons involved to be indicative of the attractions of insider dealing and it is inevitable that those concerned will continue these activities unless checked by being identified, prosecuted and, if found guilty punished".